2016
DOI: 10.1111/aos.13342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different lubricant eye gels on tear film thickness as measured with ultrahigh‐resolution optical coherence tomography

Abstract: In conclusion, we observed differences in TFT after administration of the lubricant gels. Ten minutes after instillation, a pronounced increase in TFT was observed in all groups. As compared to the other products, the combination of trehalose 3% + hyaluronic acid 0.15% offers a significantly longer increase in TFT indicating for a longer residence time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
1
28
1
1
Order By: Relevance
“…Although the observed change in TFT is small, the strength of the OCTbased measurement of TFT is that with a coefficient of variation of less than 4% the instrument is capable of detecting subtle changes in TFT in patients with DED [12]. As such, we have reported in previous experiments using the same UHR-OCT system that treatment with topical lubricants leads to a short-time increase in TFT depending on the physical properties of the agent applied [16][17][18][19]. The data of the current experiment extend these previous findings, showing that a short-time topical anti-inflammatory therapy can increase precorneal TFT.…”
Section: Discussionmentioning
confidence: 92%
“…Although the observed change in TFT is small, the strength of the OCTbased measurement of TFT is that with a coefficient of variation of less than 4% the instrument is capable of detecting subtle changes in TFT in patients with DED [12]. As such, we have reported in previous experiments using the same UHR-OCT system that treatment with topical lubricants leads to a short-time increase in TFT depending on the physical properties of the agent applied [16][17][18][19]. The data of the current experiment extend these previous findings, showing that a short-time topical anti-inflammatory therapy can increase precorneal TFT.…”
Section: Discussionmentioning
confidence: 92%
“…; Wozniak et al. ). However, no studies exist relating this to the tear turbidity and patient's symptoms.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent prospective study, the capacity to longitudinally quantify changes to tear film thickness was demonstrated in a study of 30 individuals with glaucoma who were changed from preserved topical prostaglandin therapy to a non‐preserved formulation . Similarly, the ability to quantify progressive changes in tear film thickness, as a measure of the degree of ocular retention, was reported in a cohort of patients with mild‐to‐moderate dry eye disease, following administration of a single drop of different topical lubricant products …”
Section: An Overview Of As‐oct Imaging In Humansmentioning
confidence: 99%